Correction: Liu et al. (2023). Testing the Reciprocal Effect between Value of Education, Time Investment, and Academic Achievement in a Large Non-Western Sample. Journal of Intelligence 11: 1333 - Meimei Liu; TuongVan Vu; Nienke van Atteveldt; Martijn Meeter (Journal of Intelligence)
In a recent paper, while our overall conclusion remains valid, one specific finding—that there are reciprocal relationships between how Korean students value education, the time they invest in their studies, and their academic achievements—requires correction (Liu et al [...]